Perlindungan Hukum Bagi Penyidik Polri Dalam Melaksanakan Tugas dan Fungsinya Guna Terwujud Tegaknya Hukum dan Ketertiban Dalam Perspektif Hak Azasi Manusia - Wahyu Daeni (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2018)
The Police of the Republic of Indonesia (POLRI) in relation to the Government is one of the functions of state government in the field of maintaining security and public order, law enforcement, protection, advisory and service to the community, which aims to make it happen, internal security covering the maintenance of security and public order, order and law enforcement, the implementation of protection, guidance and service to the community, and the establishment of society by upholding human rights (HAM). The police are in charge to protect the human rights of civilians. but the public often ignorant that the police, both as personal persons and profesional individual, also have human rights that must be preserved. The underlying factor behind the human right abandonment is a police assumption as a creature that transcends humanity. It make the police impossible to fall as a victim, The omnipotent (power full) state positions them as the only one who is always blamed when there is a friction between the police and the public. The purpose of this research is to find a legal protection system for the investigators who become victims while carrying out their duties from a human rights perspective and find the system of duties and functions of police investigators independently and professionally to realize law enforcement and order. This type of research is normative legal research or library research methods, namely the methods used in legal research conducted by examining existing library materials. Juridical research or normative legal research (doctrinal), is a study that examines legal issues in depth against established legal norms. The research specifications used are descriptive analytical which describes various applicable laws and regulations related to legal theories and the practice of implementing positive laws related to the problems under study. This study uses a normative juridical approach, namely research that is guided by legal norms stated in the legislation. The study was conducted on laws and regulations and legal principles which are secondary data. Based on library research, data analysis and research results, it shows that until now there is still a violation of human rights personnel, both internal and external, It make the police demoralized, then manifested into the form of unbending behavior worth it. Tragically, the most vulnerable target of demoralization is precisely the party that the police should protect, that is the community. The shape starts from poor service to the criminality that preys on society. The independence of the National Police as a tool of the state, still influenced by executive power and other extra judicial powers, as well as in law enforcement is still largely determined by intra-judicial power. Police professionalism is directed through a multi-dimensional approach to improving the quality of Polri personnel by emphasizing well motivation; well education; well salary; well trained; well equipments; supervisory function; and moral commitment.